If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = -1(2 + -6x) + 8x 7 = (2 * -1 + -6x * -1) + 8x 7 = (-2 + 6x) + 8x Combine like terms: 6x + 8x = 14x 7 = -2 + 14x Solving 7 = -2 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 7 + -14x = -2 + 14x + -14x Combine like terms: 14x + -14x = 0 7 + -14x = -2 + 0 7 + -14x = -2 Add '-7' to each side of the equation. 7 + -7 + -14x = -2 + -7 Combine like terms: 7 + -7 = 0 0 + -14x = -2 + -7 -14x = -2 + -7 Combine like terms: -2 + -7 = -9 -14x = -9 Divide each side by '-14'. x = 0.6428571429 Simplifying x = 0.6428571429
| ketquax-5=28 | | 1.7t=-68 | | (5-i)-(8-2i)=0 | | -6n-39=-7(4n-7) | | 25=y+26 | | 1.5(3n+2)=0 | | 10x-1=5x+6 | | X^2+2=624 | | 7(y-1)=3y+17 | | 2x+4+6x=44 | | 10c=15+5c | | 6w^2-365w+8550=0 | | 0.2(60)+0.005x=0.1(60+x) | | 6w^2-365+8550=0 | | 20+-a=10a+-2 | | 20x+7=4x+6 | | =(2x+3)(4x-3) | | 14p^2+p-2=4p^2 | | 5=-k | | 2x-60=2x+40 | | 325.00+6.44t=2500 | | -2(18-3n)=7n+2n | | 3(-2x-3)=-45 | | 30+8k=3(8+3k) | | 325.44+6.44t=2500 | | 2y-5=6x | | 2x-y=2x+y | | 3-3/4=6 | | 7(2x+3)=-7 | | 2.7y-6.1-0.3y=1.1 | | 5x+1=-5x+10 | | 7-3z=8+2z |